Intelligent Mobile Projects with TensorFlow - Tang, Jeff; Tang, Jeff (Packt Publishing, 2018)
Create Deep Learning and Reinforcement Learning apps for multiple platforms with TensorFlowAbout This BookBuild TensorFlow-powered AI applications for mobile and embedded devicesLearn modern AI topics such as computer vision, NLP, and deep reinforcement learningGet practical insights and exclusive working code not available in the TensorFlow documentationWho This Book Is ForIf you're an iOS/Android developer interested in building and retraining others' TensorFlow models and running them in your mobile apps, or if you're a TensorFlow developer and want to run your new and amazing TensorFlow models on mobile devices, this book is for you. You'll also benefit from this book if you're interested in TensorFlow Lite, Core ML, or TensorFlow on Raspberry Pi.What You Will LearnClassify images with transfer learningDetect objects and their locationsTransform pictures with amazing art stylesUnderstand simple speech commandsDescribe images in natural languageRecognize drawing with Convolutional Neural Network and Long Short-Term MemoryPredict stock price with Recurrent Neural Network in TensorFlow and KerasGenerate and enhance images with generative adversarial networksBuild AlphaZero-like mobile game app in TensorFlow and KerasUse TensorFlow Lite and Core ML on mobileDevelop TensorFlow apps on Raspberry Pi that can move, see, listen, speak, and learnIn DetailAs a developer, you always need to keep an eye out and be ready for what will be trending soon, while also focusing on what's trending currently. So, what's better than learning about the integration of the best of both worlds, the present and the future? Artificial Intelligence (AI) is widely regarded as the next big thing after mobile, and Google's TensorFlow is the leading open source machine learning framework, the hottest branch of AI. This book covers more than 10 complete iOS, Android, and Raspberry Pi apps powered by TensorFlow and built from scratch, running all kinds of cool TensorFlow models offline on-device: from computer vision, speech and language processing to generative adversarial networks and AlphaZero-like deep reinforcement learning. You'll learn how to use or retrain existing TensorFlow models, build your own models, and develop intelligent mobile apps running those TensorFlow models. You'll learn how to quickly build such apps with step-by-step tutorials and how to avoid many pitfalls in the process with lots of hard-earned troubleshooting tips.Style and approachThis book takes a practical, project-based approach to teach specifics of mobile development with TensorFlow. Using a reader-friendly approach, this book will provide detailed instructions and also discuss the broader context covered within.